RANCANG BANGUN SISTEM INFORMASI PENJUALAN PADA KANARA BALI BERBASIS WEB - Made Suci Ariantini; Ni Made Ari Darmayanti (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTKanara Bali is a trading company that sells various kinds of Balinese handicraft artwork. Thehandicrafts that Kanara Bali sells include garden accecories, art stone carving, water fountainand more. Kanara Bali serves direct purchases and also serves custom orders in accordance withconsumer demand. Kanara Bali have problems with the data recording process of incominggoods, goods out and stock items. The sales transaction process is only recorded using phurchaseorder (PO) paper. The problem that occurs with using phurchase order paper is the frequent lossof data contained in the phurchase order paper. The reporting process is also delayed so that thedata presented becomes less accurate. The purpose of this research is to produce the design ofsales information system on Kanara Bali based website. The system built will be used to assist thecompany in processing sales transactions, recording incoming goods data, goods out and stockitems. This application is built using waterfall development method and php programminglanguage as well as mysql as database. Stages of research starts from the stages of data analysisis by doing observation, interview and documentation, and in proceed with the design of thesystem in the form of Data Flow diagram and user interface design and the last is theimplementation of the system. The output of this research is a website-based sales applicationwhere input data in the form of sales transaction data and purchases that produce output in theform of sales reports and purchasing reports. From the existing transaction process can generatesales reports, purchases reports and stock items reports that can be viewed by the user and owner.The report can be used as consideration in the company's decision making.Keywords: sales information systems, website based applications, PHP, Mysql.ABSTRAKKanara Bali merupakan perusahaan dagang yang menjual berbagai macam hasil karya senikerajinan khas Bali. Kerajinan yang di jual Kanara Bali meliputi garden accecories, art stonecarving, water fountain dan lainnya. Kanara Bali melayani pembelian langsung dan juga melayanicustom order sesuai dengan permintaan konsumen. Kanara Bali memiliki permasalahan padaproses pencatatan data barang masuk, barang keluar dan stok barang. Proses transaksi penjualanhanya dicatat menggunakan kertas phurchase order (PO). Tujuan penelitian ini adalah untukmenghasilkan rancang bangun sistem informasi penjualan pada Kanara Bali berbasis website.Sistem yang dibangun akan digunakan untuk membantu pihak perusahaan dalam memprosestransaksi penjualan, pencatatan data barang masuk, barang keluar dan stok barang. Aplikasi inidibangun dengan menggunakan metode pengembangan waterfall dan bahasa pemrograman PHPserta mysql sebagai database. Tahapan penelitian dimulai dari tahapan analisis data yaitu denganmelakukan observasi, wawancara dan dokumentasi, dan di lanjutkan dengan perancangan sistemberupa Data Flow diagram dan rancangan user interface serta yang terakhir adalah implementasisistem. Luaran penelitian ini berupa aplikasi penjualan berbasis website dimana input data berupadata transaksi penjualan dan pembelian yang menghasilkan output berupa laporan penjualan danlaporan pembelian. Dari proses transaksi yang ada dapat menghasilkan laporan penjualan, laporanpembelian dan laporan stok barang yang dapat dilihat oleh user dan owner. Laporan tersebut dapatdijadikan sebagai bahan pertimbangan di dalam pengambilan keputusan perusahaan.Kata Kunci: sistem informasi penjualan, aplikasi berbasis website, PHP, Mysql